2006
DOI: 10.1038/sj.ijo.0803384
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between glycaemic abnormalities, obesity and insulin resistance in nondiabetic Polynesians of New Caledonia

Abstract: Objective: Polynesians in New Caledonia have an increased risk for developing diabetes, compared to Melanesians or Europeans. They are also more prone to obesity. The aim of this study was to analyse differences in the pre-diabetic state that may explain the varying susceptibility to diabetes between these three ethnic groups, focusing on the balance between insulin resistance and capacity of pancreatic cells to secrete insulin. Design and subjects: The CALDIA Study is a population-based cross-sectional survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
3
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…Our observation that prevalence of obesity is greater among adults on Futuna than on Ambae is consistent with patterns observed in other studies directly comparing Polynesians and Melanesians in other parts of the Pacific: Defay et al (2007) found that Polynesians living in New Caledonia demonstrated a slightly higher prevalence of obesity than Melanesians (41.7% versus 38.3%), and Heightmann et al (1997) reported that Samoans of Polynesian origin demonstrated greater prevalence of high BMIs than Torres Strait Islanders of Melanesian descent.…”
Section: Contributors To Differences In Adult Melanesian and Polynesisupporting
confidence: 91%
“…Our observation that prevalence of obesity is greater among adults on Futuna than on Ambae is consistent with patterns observed in other studies directly comparing Polynesians and Melanesians in other parts of the Pacific: Defay et al (2007) found that Polynesians living in New Caledonia demonstrated a slightly higher prevalence of obesity than Melanesians (41.7% versus 38.3%), and Heightmann et al (1997) reported that Samoans of Polynesian origin demonstrated greater prevalence of high BMIs than Torres Strait Islanders of Melanesian descent.…”
Section: Contributors To Differences In Adult Melanesian and Polynesisupporting
confidence: 91%
“…In a previous study, we have shown in accordance with Simmons et al (3) that Polynesians had low fasting insulin levels and HOMA-IR values (6). This may be due to their high physical activity or other environmental factors, such as diet, or to genetic factors.…”
supporting
confidence: 69%
“…Polynesians also exhibit high rates of obesity (2,3), known to be a risk factor for insulin resistance and type 2 diabetes (4,5). However, recent analyses of the CALDIA Study showed that despite high indexes of abdominal obesity, Polynesians had low fasting plasma insulin levels and homeostasis model assessment of insulin resistance (HOMA-IR) (6). Since abdominal obesity is usually associated with impaired fasting glucose, dyslipidemia, and/or hypertension, forming the metabolic syndrome (7,8), we investigated whether these features were present in this group, in comparison with Melanesians and Europeans.…”
mentioning
confidence: 99%
“…Almost all indigenous populations considered in this paper have greater prevalence of diabetes, obesity and chronic respiratory diseases such as asthma and chronic obstructive pulmonary disease [19][20][21][22][23][24][25][26][27][28][29] (Table 2).…”
Section: Health Status Of Indigenous Populationsmentioning
confidence: 99%